Dynamics of electronic transitions and frequency dependence of negative capacitance in semiconductor diodes under high forward bias - Bansal, Kanika; Henini, M.; Alshammari, Marzook S.; Datta, Shouvik (American Institute of Physics, 2014)
We observed qualitatively dissimilar frequency dependence of negative capacitance under high charge injection in two sets of functionally different junction diodes: III-V based light emitting and Si-based non-light emitting diodes. Using an advanced approach based on bias activated differential capacitance, we developed a generalized understanding of negative capacitance phenomenon which can be extended to any diode based device structure. We explained the observations as the mutual competition of fast and slow electronic transition rates which are different in different devices. This study can be useful in understanding the interfacial effects in semiconductor heterostructures and may lead to superior device functionality.